Perforation of a nasoseptal flap does not increase the rate of postoperative cerebrospinal fluid leak. Issue 4 (26th January 2015) - Huntley, Colin; Iloreta, Alfred Marc Calo; Nyquist, Gurston G.; Otten, Marc; Garcia, Hermes; Farrell, Christopher; Rosen, Marc R.; Evans, James J.
<x xml:space="preserve">Abstract</x> Background The nasoseptal flap (NSF) has been shown to be a valuable addition to the reconstructive armamentarium of the endoscopic skull‐base surgeon. We aimed to evaluate the rate of postoperative cerebrospinal fluid (CSF) leak after use of a NSF that had a small tear during harvest. Methods After Institutional Review Board (IRB) approval, we analyzed our database of patients undergoing skull‐base resection. We included all patients who had a NSF reconstruction, septoplasty, and/or spur on preoperative computed tomography (CT) imaging. We then evaluated video of each procedure to determine if a tear occurred in the NSF during harvest. Patient records were reviewed to determine if a postoperative CSF leak occurred. Results We evaluated video of 21 patients who underwent a skull‐base resection, were reconstructed with a NSF, and had either a septoplasty or evidence of a septal spur on CT imaging. Of these 21 cases, 11 small tears occurred during harvest of the NSF flap and none of the patients with a torn NSF had a postoperative CSF leak. Conclusion Our series shows a 0% postoperative CSF leak rate in patients undergoing skull‐base reconstruction with a NSF that was torn during harvest. Small tears in the NSF do not seem to affect postoperative CSF leak rates.